Assessing pedestrian facilities on crossing bridges - Desriani, Rian Wulan; Komardjaja, Inge (2008)
In 2003, seven pedestrians were killed and 41 pedestrians injured in collisions with motor vehicles when pedestrians crossed the roads in Bandung City. In order to reduce such casualties, there are some alternative road crossings, such as the pelicans, zebra crossings, toucan crossings and pedestrian bridges. From these alternatives, big cities in Indonesia tend to construct pedestrian bridges because of the tax that is obtained from the billboards that hang on both sides of these bridges. The planning of these bridges was based only on the number of vehicles that pass the road from both directions, and the number of pedestrians who cross the road. This study identifies location factors of the existing pedestrian bridges in Bandung City. The field study is done by collecting data from different attributes and compare them with the use rate of each bridge. The analysis of the data focuses on the characteristics of activities, pedestrians, and roads .The purpose of the study is to inform planners and designers about the location factors to increase the use rate. In reality, the average use rate of the sixteen pedestrian bridges in Bandung City is low (25,22%). Many pedestrians continue to cross the roads at-grade by risking their lives, rather than having to walk the extra distance to the bridge, which they perceived as a waste of time and energy. In the planning of pedestrian crossing bridges other factors have to be considered, apart from the traffic volume and the number of pedestrians. In the layout design, the accessibility to the bridges have to be heeded. But, it is strongly suggested that constructing pedestrian bridges will be the last choice of crossing the roads.